System design with memristor technologies - Guckert, Lauren; Swartzlander, Earl E., Jr., 1945- (Materials, circuits and devices series ;, 2018)
Memristors are a new class of circuit element with the ability to change their resistance value while retaining memory of their current and past resistances. Their small form factor, high density, and fast switching times have sparked research into their applications in modern memory hierarchies. However, these new components pose system design challenges, as well as opportunities. System Design with Memristor Technologies explores design solutions for memristors, covering research and development trends in memristor technology, fabrication, modelling, and applications, and the design and implementation of arithmetic units using memristors. The book begins with an introduction to the principles of system design with memristors, then goes on to address memristor logic gates, arithmetic units for adders, multipliers and dividers, and improved and optimised adder, multiplier and divider designs. The final chapters draw conclusions from the topics covered and explore potential future trends in research into system designs with memristor technologies. This book is essential reading for research scientists and electronics engineers interested in the use of memristors in future system architectures, specifically focused on the areas of arithmetic units, non-Von-Neumann architectures, and logic-in-memory